Bringing compassion into information systems research: A research agenda and call to action. (March 2019) - Raman, Roopa; McClelland, Laura
In this article, we assert that compassion-driven approaches are the sustainable way for information and communication technologies to contribute to economic value. We urge future information systems research to emphasize, with equal vigor, the joint goals of compassion and financial gains from information and communication technologies. We present a broad agenda for future information systems research based on this premise. We also discuss how certain core assumptions underlying traditional information systems research—so far, driven primarily by economic value as outcome—would need to change in order to support this new agenda emphasizing compassion and economic value as complementary and synergistic outcomes. We provide a brief concrete illustration of this proposed agenda, and its underlying revised assumptions, by drawing on the example of a prominent field of study in information systems research, namely health information systems research.